Plasma-activated media inhibits epithelial-mesenchymal transition and ameliorates intestinal fibrosis through the PPARγ/TGF-β1/SMAD3 pathway - Yi You; Yaping Shen; Yan Yang; Xiaoyang Wei; Yuheng Zhou; Foxing Tan; Longcheng Deng; Haolin Du; Sen Wang; Cheng Wang; Yan Huang (PLoS ONE, 2025)
Inflammatory bowel disease often complicates intestinal lumen stenosis, and intestinal fibrosis is the core pathological process leading to its development. Currently, there are no effective drug treatments available to prevent or improve intestinal fibrosis. Previous studies have shown that PAM (plasma-activated media) inhibits epithelial-mesenchymal transition (EMT) and improves skin fibrosis by regulating the PPARγ/TGF-β1 axis. However, it is unclear whether PAM can improve intestinal fibrosis. We used a gradient concentration of PAM to intervene in the dextran sulfate sodium (DSS)-induced mouse intestinal fibrosis model to evaluate its effects onalleviating fibrosis and explore the specific molecular mechanisms. In addition, we used PAM to intervene in the TGF-β1-induced rat intestinal crypt epithelial cell (IEC-6) EMT and fibrosis in an in vitro model to further explore the molecular mechanisms by which PAM improves intestinal fibrosis. We found that PAM can improve intestinal fibrosis by inhibiting epithelial-mesenchymal transition through the PPARγ/TGF-β1/SMAD signaling pathway.